Peran Manajemen Gereja dalam Mengembangkan Pelayanan Bagi Remaja di Gereja HKBP Cipayung Cilangkap di Era Society (5.0) - Sanga Harapan; Djoys Anneke Rantung; Lamhot Naibaho (Journal on Education, 2023)
The Covid-19 pandemic that has been experienced by the whole world for the last 2 years (2020 and 2021), has changed many things in the order of human life, this is also being felt in the world of ministry or the Church. Where the Church must also improve itself in dealing with the changes that occur, especially in the field of ministry for youth in the church. And this can be achieved if the church has good management in managing existing services. The purpose of this research is to explain the role of church management in developing services for youth in the Cipayung Cilangkap HKBP (Huria Batak Kristen Protestant) church after the C-19 pandemic, where the church must continue to provide the best service for the congregation in this difficult situation. The life of the youth in the church is one of the important things that must be kept in mind in church management. A shocking data was revealed by Zega, in an article which stated that 50% of the current millennial generation have left the church. This is a challenge for the church so that to deal with this problem, the church must prepare the best service for its people and this can only be achieved with good management in the ministry of the church. The results of the research prove that one of the things that triggers the problem above is the poor management of the church and this is also exacerbated by technological developments which also affect the lifestyle of young people in the church. The method used is the method of library research (library research) and descriptive research.